Pengaruh Motivasi, Komitmen Kerja dan Telework Terhadap Produktifitas Kerja dengan Teknologi Informasi Sebagai Variabel Moderasi (Studi Kasus: Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan) - Arumsari, Ratu Rayanti; Fahruddin Salim; Lies Putriana (Lembaga Pengembangan Kinerja Dosen, 2022)
The prolonged COVID-19 pandemic requires humans to limit their movements and activities, in this case office activities. This is a new challenge for workers in fulfilling their jobs who have to work remotely with limited facilities. These conditions require employees to remain motivated in fulfilling their responsibilities, maintain commitment to the organization while continuing to carry out dual roles at home as individuals and workers during the implementation of the telework scheme or known as Working from Home (WFH). The purpose of this study was to determine the effect of work motivation, work commitment, telework, and information technology on work productivity. In addition, to determine the effect of technology on work motivation, work commitment and changes in the work environment in decreasing work productivity. This research is quantitative research with survey method. The time for conducting the research is July 1, 2020 to December 30, 2020 at the office of the Coordinating Ministry for Human Development and Culture, which is also the population of this research. The sample used proportioned stratified random sampling and obtained 166 respondents according to the criteria. The data analysis technique used SEM software PLS. The results show that motivation has a significant effect on work productivity, commitment has a significant negative effect on work productivity, telework has a significant effect on work productivity, information technology has no significant effect on the relationship between motivation and work productivity. Information technology has no significant effect on the relationship between work commitment and work productivity. Information technology has a significant effect on the relationship between telework and work productivity. technology has a significant effect on work productivity.